Junctional force patterning drives both positional order and planar polarity in the auditory epithelia - Anubhav Prakash; Julian Weninger; Nishant Singh; Sukanya Raman; Madan Rao; Karsten Kruse; Raj K. Ladher (Nature Communications)
Abstract Tissue function depends on the precise organisation of the constituent cells. In the cochlea, the fidelity of hearing depends on mechanosensory hair cells being consistently surrounded by supporting cells. In addition to this positional order, auditory sensitivity depends crucially on planar cell polarity. This is characterised by the alignment of the orientation of eccentrically placed hair bundles on each hair cell. These two levels of order emerge simultaneously despite the cellular fluxes that occur during cochlear development. However, the link between tissue-scale cellular rearrangements and intrinsic cellular mechanisms remains unknown. By combining experimental and theoretical approaches, we find a precise force patterning underpinning positional order and planar cell polarity. This occurs through the modulation of the levels and phospho-type of the regulatory light chain of non-muscle myosin II at specific cell-cell junctions of the auditory epithelium. We propose that the control of junctional mechanics is vital for the organisation of multi-cell-type epithelia.